PENGARUH SERTIFIKASI PENDIDIK TERHADAP KINERJA KONSELOR DALAM PELAKSANAAN LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH - Mudjijanti, Fransisca (Widya Warta, 2018)
The purpose of this study was to analyze the differences between the performance of counselors having educator certification and those having no educator certification in providing guidance and counseling services in schools. The population of this study were all counselors of junior high schools, senior high schools, vocational high schools, in the City of Madiun. The research samples taken with purposive sampling technique were 62 counselors consisting of 31 counselors who were certified and 31 counselors who were not.The data collection technique was a questionnaire with 4 alternative answers. The data analysis technique was descriptive percentage (DP and t-test. Descriptive percentage analysis results showed that the performance of counselors having sertification and the performance of those having no certification were both excellent in the implementation of guidance and counseling services in schools. The mean of the performance of counselors having educator certification was 1.1 higher than the mean score of the performance of counselors having no educator certification. The results of the t test showed a significant value of 0.718 > the value of Î± (0.05), then Ho was rejected meaning there is no effect of educator certification on the performance of counselors in carrying out guidance and counseling services in schools.